2001
DOI: 10.1021/es991320p
|View full text |Cite
|
Sign up to set email alerts
|

On-Road Particulate Matter (PM2.5 and PM10) Emissions in the Sepulveda Tunnel, Los Angeles, California

Abstract: Total and speciated particulate matter (PM2.5 and PM10) emission factors from in-use vehicles were measured for a mixed light- (97.4% LD) and heavy-duty fleet (2.6% HD) in the Sepulveda Tunnel, Los Angeles, CA. Seventeen 1-h test runs were performed between July 23, 1996, and July 27, 1996. Emission factors were calculated from mass concentration measurements taken at the tunnel entrance and exit, the volume of airflow through the tunnel, and the number of vehicles passing through the 582 m long tunnel. For th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
63
3
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(83 citation statements)
references
References 29 publications
16
63
3
1
Order By: Relevance
“…OC/EC in WZS tunnel ranged from 0.48 to 1.45 with an average value of 0.86. Emission factors of OC and EC in WZS tunnel were similar to those reported in Sepulveda tunnel (Gillies et al, 2001). Table 2 showed that EFs of water soluble ions including SO ions in WZS and Zhujiang tunnels (He et al, 2008) were in the same order (of magnitude).…”
Section: Oc and Ecsupporting
confidence: 82%
See 1 more Smart Citation
“…OC/EC in WZS tunnel ranged from 0.48 to 1.45 with an average value of 0.86. Emission factors of OC and EC in WZS tunnel were similar to those reported in Sepulveda tunnel (Gillies et al, 2001). Table 2 showed that EFs of water soluble ions including SO ions in WZS and Zhujiang tunnels (He et al, 2008) were in the same order (of magnitude).…”
Section: Oc and Ecsupporting
confidence: 82%
“…As shown in Table 1, the EFs of PM 2.5 in the WZS tunnel was 70.1 ± 15.9 mg·veh −1 ·km −1 , whereas it was 22.2 ± 6.52 mg·veh −1 ·km −1 in the KXL tunnel. ; It is known that, the PM 2.5 EFs of vehicles could be influenced by many factors, such as vehicle type (Cheng et al, 2010;He et al, 2008), fuel quality (Yue et al, 2015), model year of the vehicles (Liu et al, 2009;Shah et al, 2006), vehicle speed (Gillies et al, 2001), and the features of the road (Pio et al, 2013). EFs of PM 2.5 in this study were compared with those from other tunnel studies in China (Table 1).…”
Section: Emission Factors Of Pm 25 and Comparison With That From Othmentioning
confidence: 99%
“…Similarly, NO 3 -/EC and NO 3 -/OC ratios were found to be 0.40 ± 0.11, 0.55 ± 0.21, 0.34 ± 0.22 and 0.93 ± 0.23, 1.23 ± 0.32, 1.23 ± 0.43 for R, C and I sites respectively. These ratios of NO 3 -/EC and NO 3 -/OC are higher than those calculated from road tunnel aerosols (0.1 for NO 3 -/EC and 0.09 for NO 3 -/OC) (Gillies et al, 2001) indicating that vehicular as well as biomass burning activities are contributing at all receptor sites.…”
Section: Levels Of Carbonaceous Mattercontrasting
confidence: 57%
“…38,39 The OC/TC fraction of PM 2.5 released by mixed traffic in the Sepulveda Tunnel in Los Angeles was 0.47. 40 This fraction was 0.7 for PM 2.5 released from mixed traffic in a tunnel in Milan, Italy, 41 and 0.28 and 0.6, respectively, for heavy-duty diesel vehicles and light-duty vehicles in the Caldecott Tunnel east of Oakland, CA. 22 Shah et al 42 used a mobile emissions laboratory attached to the tailpipe of heavy-duty diesel trucks to measure OC and EC emissions under varying driving conditions.…”
Section: Emission Estimation Methods and Magnitude Of Emissionsmentioning
confidence: 95%